Le timbre-poste entre sens textuel et sens pratique - Hani Georges (Communication)
Viewing the postage stamp as a semiotic object, rather than simply a sign, means recognizing that it plays a certain role in a significant practice that encompasses multiple aspects, including processes, actants, communication context, and narrative structure. The postage stamp can thus convey — and take on — diverse meanings within communications processes. Drawing on the integration process proposed by Jacques Fontanille, the author conducts a semiotic analysis of practices where the postage stamp can function as a semiotic object in and of itself, such as postage, recognition, and personalization.